2015
DOI: 10.1007/s11751-015-0226-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 1 % silver sulphadiazine dressings in preventing infection of external fixation pin-tracks: a randomized study

Abstract: Pin-track infection (PTI) is a common complication of external fixation. Antimicrobial dressings of the pin-site interface should reduce the severity and incidence of PTI. This study is aimed at determining the efficacy of 1 % silver sulphadiazine dressings in preventing PTI in external fixation. We compared the incidence of PTI between group A (dry sterile gauze dressing) and group B (1 % silver sulphadiazine impregnated gauze dressing). PTI was diagnosed when there was: (1) redness around any pin-site, (2) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Although many investigators have looked into this, a conclusion on the efficacy of certain dressings alone is not possible because the study groups differ in other aspects of pin site care or surgical technique. Seven randomized trials were identified that were designed to specifically evaluate the efficacy of various dressings in reducing pin site infection rate [ 1 , 4 , 15 , 18 , 37 , 60 , 61 ]. Lee and colleagues [ 60 ] determined that pin infection rate was lower in patients undergoing limb lengthening procedures with a polyhexamethylene biguanide dressing as compared to dry gauze (1.0 versus 4.5 %, respectively); however, no deep infections occurred in either group.…”
Section: Evidence For Prevention Of Pin Site Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many investigators have looked into this, a conclusion on the efficacy of certain dressings alone is not possible because the study groups differ in other aspects of pin site care or surgical technique. Seven randomized trials were identified that were designed to specifically evaluate the efficacy of various dressings in reducing pin site infection rate [ 1 , 4 , 15 , 18 , 37 , 60 , 61 ]. Lee and colleagues [ 60 ] determined that pin infection rate was lower in patients undergoing limb lengthening procedures with a polyhexamethylene biguanide dressing as compared to dry gauze (1.0 versus 4.5 %, respectively); however, no deep infections occurred in either group.…”
Section: Evidence For Prevention Of Pin Site Infectionsmentioning
confidence: 99%
“…Lee and colleagues [ 60 ] determined that pin infection rate was lower in patients undergoing limb lengthening procedures with a polyhexamethylene biguanide dressing as compared to dry gauze (1.0 versus 4.5 %, respectively); however, no deep infections occurred in either group. Ogbemudia et al [ 61 ] concluded that a 1 % silver sulphadiazine dressing reduced pin track infection rates in a population comprised mostly of trauma patients (1.9 % of pin sites, as compared to 14.2 % with dry gauze). However, Yuenyongviwat and Tangtrakulwanich [ 1 ] found no differences between these dressing types in the setting of tibial external fixators used for trauma (46.7 % of patients with pin track infections with silver sulphadiazine dressings versus 40.0 % with dry gauze).…”
Section: Evidence For Prevention Of Pin Site Infectionsmentioning
confidence: 99%
“…W-Dahl and Toksvig-Larsen [ 6 ] compared a chlorhexidine 2 mg/ml solution and sodium chloride 9 mg/ml solution and reported that PTI was found in 9 % of the chlorhexidine group and in 17 % of the sodium chloride group. Polyhexamethylene biguanide or 1 % silver sulfadiazine-impregnated gauze dressing of the pin site has been recommended to prevent PTI [ 14 , 15 ]. We routinely use once-daily pin site care with chlorhexidine 2 mg/ml solution, but we need to search further to determine whether it is the most appropriate method.…”
Section: Discussionmentioning
confidence: 99%
“…SSD is a highly effective topical antimicrobial agent with slow release of silver ions that can inhibit the growth and proliferation of bacteria. [33][34][35] SSD has been the standard treatment for burn wounds over the past two decades. [36][37][38] It is still the most frequently used topical agent in the treatment of infections.…”
Section: Discussionmentioning
confidence: 99%